2019
DOI: 10.12963/csd.19657
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of Syllable Structure in Jordanian Arabic

Abstract: The aim of this research was to investigate the early word syllable structure and notable phonological processes in the speech of Jordanian Arabic (JA)-speaking children. Methods: Elicited and spontaneous speech productions of 20 children were transcribed and analyzed by syllable structure. The ages of the participants ranged from 1 to 3 years, divided into four age groups: 1;0-1;6, 1;7-2;0, 2;1-2;6, and 2;7-3;0. Then, the data was analyzed according to ten phonological processes influencing word syllable stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Overall, these observations highlight the specific speech sound Although certain error patterns, such as weak syllable deletion and cluster reduction, are universal (Ayyad, 2011;Bauman-Waengler, 2008;Mashaqba et al, 2019;So & Dodd, 1995), specific errors are language-specific. For instance, in this study, the production of emphatics, gutturals, and geminates poses a challenge to Arabic-speaking children.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…Overall, these observations highlight the specific speech sound Although certain error patterns, such as weak syllable deletion and cluster reduction, are universal (Ayyad, 2011;Bauman-Waengler, 2008;Mashaqba et al, 2019;So & Dodd, 1995), specific errors are language-specific. For instance, in this study, the production of emphatics, gutturals, and geminates poses a challenge to Arabic-speaking children.…”
Section: Resultsmentioning
confidence: 83%
“…For example, in the word madrasa (school), the consonant in the coda position is deleted, resulting in ma.ra.sa. Consonant deletion primarily affects consonants in the coda position due to the obligatory nature of onsets in Arabic syllable structure (Mashaqba et al, 2019;Watson, 2002). It is worth noting that no instances of coda deletion were reported in the TD were in polysyllabic words.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…They found that in some Arabic dialects, the syllable final gutturals are avoided in these dialects by a metathesis process, resulting in an onset clustering. Likewise, Mshaqba et al . (2019) addressed the early word syllable structure and the remarkable phonological processes in the speech of Jordanian Arabic (JA)-speaking children.…”
Section: Theoretical Backgroundmentioning
confidence: 89%
“…, plus a coda. Onset is an obligatory component in Arabic syllable structure, and thus in the case of onsetless syllables the prosthetic glottal stop/ʔ/ surfaces before utterance-initial syllables (cf Watson 2002;Huneety 2015;Mashaqba et al, 2019)…”
mentioning
confidence: 99%